2021
DOI: 10.1097/cce.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Whole-Room Atomizing Disinfection System on Healthcare Surface Contamination, Pathogen Transfer, and Labor Efficiency

Abstract: Objectives: Healthcare surfaces contribute to nosocomial disease transmission. Studies show that despite standard guidelines and practices for cleaning and disinfection, secondary infection spread among healthcare workers and patients is common in ICUs. Manual terminal cleaning practices in healthcare are subject to highly variable results due to differences in training, compliance, and other inherent complexities. Standard cleaning practices combined with no-touch disinfecting technologies, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this study, the defect rectification of CSSD based on the JCI standards mainly involved "reduction of medical-related infection risk" in part II of the patient-centered standards, "infection prevention and control" in part III of the medical institution management standards, and other quality improvement chapters such as patient safety, leadership and management, facility management and safety, and information management, etc. (14). The results showed that the hospital management effect was significantly improved and the quality has been continuously enhanced.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the defect rectification of CSSD based on the JCI standards mainly involved "reduction of medical-related infection risk" in part II of the patient-centered standards, "infection prevention and control" in part III of the medical institution management standards, and other quality improvement chapters such as patient safety, leadership and management, facility management and safety, and information management, etc. (14). The results showed that the hospital management effect was significantly improved and the quality has been continuously enhanced.…”
Section: Discussionmentioning
confidence: 94%
“…Although the aerial way is accepted as the main transmission route of SARS-CoV-2, the transmission of the disease by contaminated surfaces cannot be discarded, mainly in healthcare environments [39] . Regardless the contribution of contaminated surfaces on the virus transmission, there are robust experimental evidences that the whole-room disinfection systems based on disinfectant atomized aerosols or gases like the ozone together conventional cleaning procedures reduces significantly microbial contamination of surfaces [15] , [40] .…”
Section: Introductionmentioning
confidence: 99%